(untitled) (Journal of the College of Basic Education, 2022)
It is represented in the negative effect of psychological stress on the players before the competition because it is one of the most important psychological variables that the player faces.As for the research problem, it crystallized in not using the trainers and specialists (the psychological stress scale), and therefore some trainers and specialists are ignorant of the extent of the level of psychological pressure that the player is exposed to before the competition, and whether it differs from one player to another and from one region to another, noting that the premium class clubs include the northern and central regions of Iraq that It is under current research.